State of the art on tribological behavior of polymer matrix composites reinforced with natural fibers in the green materials world - Omrani, Emad; Menezes, Pradeep L.; Rohatgi, Pradeep K. (Engineering science and technology, an international journal, 2016)
Natural fiber reinforced polymer composites have emerged as a potential environmentally friendly and cost-effective alternative to synthetic fiber reinforced composites. Therefore, in the past decade, a number of major industries, such as the automotive, construction and packaging industries, have shown a considerable interest in the progress of new natural fiber reinforced composite materials. The availability of natural fibers and the ease of manufacturing have tempted researchers to study their feasibility of their application as reinforcement and the extent to which they satisfy the required specifications in tribological applications. However, less information concerning the tribological performance of natural fiber reinforced composite material is available in the literature. Hence, the aim of this bibliographic review is to demonstrate the tribological behavior of natural fiber reinforced composites and find a knowledge about their usability for various applications that tribology plays a dominant role. This review presents the reported work on natural fiber reinforced composites with special reference to the type of fibers, matrix polymers, treatment of fibers and test parameters. The results show that composites reinforced with natural fibers have an improvement in tribological properties and their properties are comparable with conventional fibers. In addition, fiber treatment and fiber orientation are two important factors can affect tribological properties where treated fibers and normal oriented fibers exhibit better friction and wear behavior. This review is trying to evaluate the effect of test parameter including normal load and sliding speed on tribological properties, and the results vary based on type of reinforcement. Generally, due to their positive economic and environmental aspects, as well as their good tribological properties, natural composites are showing a good potential for employing in several applications.